THE WILL OF THE PATIENT IN THE MEDICAL CONTRACT IN THE WORLD (World Bulletin of Management and Law, 2023)
The discussion was modest in when it is regards to some medical issues, generally Associated with the patient, especially any concept will of patient in the medical contract supple hand of law where this research consists of introduction and four discussions. The introduction is about the legal nature of the medical responsibility and most prominent differences between liability in the case of contract and in the case of neglect. The second topic was the role of the legal nature of the body of man is in the two demands and the third section revolves around the increasing gravity of bodily injury to an injured resulting from neglect. The fourth matter is the last in the types of damage and medical staff action for compensation because of the lack of resources in this matter nine source of research have chosen which are brought in the reference section
Keywords: The contract medical; The human body; The legal nature